Evaluation of rearing and feed management of native chickens in Margomulyo Village, South Lampung Regency - Fitria Tsani Farda; Khaira Nova; Etha Azzah Hasiib; Rudy Sutrisna (Community Empowerment, 2021)
Up to now, native chickens have been mostly reared traditionally, with a feeding system that does not take into account the needs of the livestock. The purpose of community service is to provide advice on the rearing system and feed management for native chickens, as well as information on feed formulations. Community service activities are carried out in Margomulyo Village, Jati Agung District, South Lampung Regency, using the Participation Rural Appraisal (PRA) method, with active participation from smallholder farmers. Farmers' increased knowledge, among other things, better understands the intensive native chicken rearing system, the potential of local feed resources, and the needs of livestock and how to formulate rations for native chickens.